Turbulent Intensity of Blood Flow in the Healthy Aorta Increases With Dobutamine Stress and is Related to Cardiac Output - Sundin, Jonathan; Bustamante, Mariana; Ebbers, Tino; Dyverfeldt, Petter; Carlhäll, Carl-Johan (Frontiers in Physiology, 2022)
Introduction The blood flow in the normal cardiovascular system is predominately laminar but operates close to the threshold to turbulence. Morphological distortions such as vascular and valvular stenosis can cause transition into turbulent blood flow, which in turn may cause damage to tissues in the cardiovascular system. A growing number of studies have used magnetic resonance imaging (MRI) to estimate the extent and degree of turbulent flow in different cardiovascular diseases. However, the way in which heart rate and inotropy affect turbulent flow has not been investigated. In this study we hypothesized that dobutamine stress would result in higher turbulence intensity in the healthy thoracic aorta. Method 4D flow MRI data were acquired in twelve healthy subjects at rest and with dobutamine, which was infused until the heart rate increased 60% when compared to rest. A semi-automatic segmentation method was used to segment the thoracic aorta in the 4D flow MR images. Subsequently, flow velocity and several turbulent kinetic energy (TKE) parameters were calculated in the ascending aorta, aortic arch, descending aorta and whole thoracic aorta. Results With dobutamine infusion there was an increase in heart rate (66±9 vs. 108±13 bpm, P<0.001) and stroke volume (88±13 vs. 102±25 mL, P<0.01). Additionally, there was an increase in Peak Average velocity (0.7±0.1 vs. 1.1±0.1 m/s, P<0.001, Peak Max velocity (1.3±0.1 vs. 1.9±0.2 m/s, P<0.001), Peak Total TKE (2.9±0.7 vs. 8.0±2.2 mJ, P<0.001), Peak Median TKE (36±7 vs. 93±24 J/m3, P=0.002) and Peak Max TKE (176±33 vs. 334±69 J/m3, P<0.001). The relation between cardiac output and Peak Total TKE in the whole thoracic aorta was very strong (R2=0.90, P<0.001) Conclusion TKE of blood flow in the healthy thoracic aorta increases with dobutamine stress and is strongly related to cardiac output. Quantification of such turbulence intensity parameters with cardiac stress may serve as a risk assessment of aortic disease development.